(untitled) (International Journal of Engineering and Computer Science, 2017)
Margins in handwriting reflect an individual’s personality. Margins could either be narrow or wide with each showing certain personality traits about the writer. Narrow left margin indicate writer is attached to his past than to his future. Wide left margin indicates writer leaves behind ones past and continue moving. A wide right margin indicates writer may be afraid to take a future step. A narrow right margin indicates writer may be willing to take a forward step and that he may not be experiencing uncertainties at that period of his life. Balanced size indicates the writer balanced person when it comes to risk taking. The handwriting of 100 adults was submitted for graph logical analysis. The graphologist’s answers to questions on the patient’s personality, her description of his character and her assessment of his inclination towards past ,present and current were checked by the person’s own answers to the questionnaire, by the personality descriptions in the case-sheets, and by the results of the Progressive Matrices Test. In this work carried, the performance was as high as 95%. The feature extraction was done using Zernike moments.